A Ticking Time Bomb in the Heart: A Case Report of Cardiac Myxoma - Reynold Siburian; Teuku Muhammad Haykal Putra; Ismail Dilawar; Gusti Reza Ferdiansyah; Meilana Saraswati (The Indonesian Heart Association, 2026)
Background: Cardiac myxoma is the most common primary cardiac tumor and is frequently found in the left atrium. Symptoms and signs are most often non-specific, making diagnosis difficult. We present a case report of an atrial cardiac myxoma with an atypical presentation. Case Illustration: A 55-year-old man presented to our outpatient clinic with recurrent and intermittent chest discomfort that had lasted for months. No other cardiac symptoms such as dyspnea or palpitations were noted. The patient’s medical history was positive for hypertension and smoking. Thorough chest pain evaluations were conducted, there were no ST-T changes on electrocardiogram. However, Transthoracic Echocardiography (TTE) revealed an incidental finding of a 2.1 x 2.6 cm mass, located in the Right Atrium (RA), with the stalk attached to the interatrial septum. Subsequently, patient was consulted to cardiothoracic surgeon and underwent successful tumor resection via median sternotomy. The tumor was confirmed histopathologically. Conclusion: The nonspecific symptoms of cardiac myxomas pose a diagnostic conundrum to clinicians. TTE plays a pivotal role in diagnosis, and surgical removal of the mass should be undertaken as soon as possible. Early detection and intervention remain imperative to rid the risk of this cardiac pathology.